Effects of Host and virus related factors on Interferon-α+ribavirin and Pegylated-interferon+ribavirin treatment outcomes in Chronic Hepatitis C patients - Akram, Madiha (BioMed Central, 2011)
BACKGROUND: Current standard therapy commonly followed for chronic Hepatitis C Virus (HCV) in Pakistan is interferon alpha plus ribavirin combination therapy (IFN α/ribavirin) and pegylated interferon plus ribavirin (PegIFN/ribavirin). PegIFN/ribavirin has increased rate of sustained virological response than standard IFN α/ribavirin therapy. Objective of current study was to analyze rate of early and delayed response to antiviral treatment as well as rate of relapse response in patients following standard treatment IFN α/ribavirin and in patients following pegylated interferon treatment. METHODS: Baseline serum samples of 153 patients enrolled for IFN α/ribavirin and 50 patients for PegIFN/ribavirin were collected. After total RNA extraction, genotyping was and HCV RNA viral load was done. Subsequently HCV RNA viral load was estimated at 4 weeks of treatment, at 12 weeks, at 24 or 48 weeks and finally after 6 months follow up period. All the data was statistically analyzed using fisher's exact test. RESULTS: Total 86 patients out of 153 patients following conventional IFN α/ribavirin therapy completed treatment and 69% of them showed Rapid Virological Response (RVR). Whereas 50 patients following PegIFN/ribavirin treatment completed treatment and 80% of them achieved RVR. Total 64 out of 86 patients following IFN α/ribavirin therapy completed follow up period and 53.5% of them achieved Sustainded Virologcal Response (SVR). Forty-five out of total 50 patients who received PegIFN/ribavirin treatment completed 6 months follow up period and among these 70% achieved SVR. SVR rates were significantly associated with RVR (p < 0.001), age (p < 0.001) and gender (p < 0.01) CONCLUSIONS: Rate of sustained virological response can be determined by factors like rapid virological response and age since they share significant association with one another. More over rate of SVR was more prominent in males than in females.